Preparing general teachers to work in inclusive classrooms: An exploratory collective case study of two Elementary and Early Childhood (K-grade 3) teacher education programmes in the United Arab Emirates - ALMEHAIRI, KALTHAM RASHED ALYATEEM (2018)
The issue of including students with disabilities in general schools is getting more and more attention from leadership and educational authorities in the United Arab Emirates (UAE). Although initial teacher education for inclusion is an area that has been widely researched on the international level, little is known about how elementary general pre-service teachers with expertise in teaching students with disabilities are prepared in the UAE’s educational context. This exploratory case study investigated the current state of how teacher programmes in two government universities in the UAE were preparing prospective teachers to work in inclusive classrooms. Curriculum used in course work and how inclusive teaching strategies and practices are addressed in this curriculum were examined. The study also explored pre-service teachers and faculty views about the contribution of these programmes to prepare prospective teachers to teach in inclusive settings. The rationale for choosing government universities was that they are the main feeders of national UAE teachers who usually join government schools and are expected to impact the future of public education in the country. These universities are also working in alignment with the UAE education policies and national vision. This study employed a qualitative research approach and a multi-case study methodology that takes interpretivism as its philosophical foundation. Data was collected by the methods of document analysis, interviews with faculty members in elementary and early-childhood (Pre K-grade 3) programmes, and focus groups with the pre-service teachers. Findings showed that there were no clear philosophies of inclusive education with regards to students with special needs guiding both programmes' frameworks. There were also major differences between the two cases in the contribution to the process of preparing their teaches for inclusive schools. The differences were mostly in linking theoretical content with practice, the quantity and the quality of field experiences, collaboration between faculty of elementary and special education, and the alignment between courses' objectives, outcomes, and educational resources regarding inclusive practices. One distinct finding in Programme (A) was that the faculty views about inclusion inclined to consider mainstreaming for students with disabilities rather than full membership to be educated in general classrooms. This view was in contrast with the views of faculty in Programme (B) who showed a strong commitment toward the principles of equity and equality in education which consequently was reflected in teaching practices. Moreover, the main challenge facing programme (A) specifically "[was] not the lack of knowledge or standards, but putting it into practice in diverse contexts" (Hollenweger, Pantić & Florian 2015, p. 11). From another perspective pre-service teachers who were interviewed in both programmes acknowledged the positive impact of the knowledge and training on preparing them to work with diverse learners. However, they expressed different challenges faced in their internship training. In programme (A) the main challenges were the lack of training on differentiation strategies and the lack of assistive services for teaching students with disabilities. While the main challenge for the pre-service teachers in Programme (B) was facing negative school culture regarding the inclusion of students with disabilities. The importance of this study is to raise awareness about the offerings of teacher education programmes in the UAE regarding preparing teachers for inclusion, and the need to make foundational changes in curriculum content to meet this aim and additionally, to pay more attention to the elementary pre-service teachers' opinions about their preparation to teach in inclusive schools.